FISTULA MANAGEMENT DUE TO CHRONIC INFECTION OF RADICULAR CYST - Tichvy Tammama; Winda Afrilia Megayanti (Fakultas Kedokteran Gigi Unjani, 2021)
A radicular cyst is the most common odontogenic cyst that arises from the epithelial residues in the periodontal ligament due to periapical periodontitis following death and necrosis of the pulp. A fistula may form a cyst with a pulp infection that produces pus and seeks its way out to the gingival surface to create a canal. The purpose of this case report is to report the management of a patient with a chronically infected radicular cyst with fistula while retaining the involved tooth. A case report was a 13-year-old female patient who came to Department Oral Surgery of a hospital with a complaint of a lump in the front gum and palate that didn't heal for two years ago and often discharged pus. Intraoral examination showed a lump in the gingiva and palate with fistula in the interdental gingiva of teeth 11-12 with soft consistency and pain with palpation. Panoramic results showed characteristics of the radicular cyst at the 13-11 tooth region. The lesion is diagnosed as a chronic infection of a radicular cyst due to pulp necrosis in teeth 12-11 with interdental fistulas. Biopsy enucleation of the cyst was performed with teeth preservation. The patient was advised to have regular check-ups. On the sixth month of control, the surgical wound was good, without any complaints and signs of recurrence. The result is that a radicular cyst can become chronically infected and form a fistula that oozes pus into the oral cavity. The cyst can be treated with enucleation biopsy and fistulectomy with the preservation, without any recurrences. DOI : 10.54052/jhds.v1n2.p209-218